PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP STRUKTUR MODAL PERUSAHAAN : Dibuat Oleh Alien Akmalia - Alien Akmalia (Neraca, 2022)
The purpose of this study was to examine the effect of profitability and liquidity on the company's capital structure. Profitability variable is proxied by Return on Equity (ROE), Liquidity is proxied by Current Ratio (CR) and Capital structure is proxied by Debt to Equity Ratio (DER). The object of research used in this study is the consumer goods industry sector companies listed on the Indonesia Stock Exchange for the period 2016 to 2020. The sampling technique used is purposive sampling technique and obtained samples that meet the criteria as many as 101 samples. The data analysis technique used is multiple linear regression using the SPSS program. The results showed that liquidity was proven to have a significant negative effect on capital structure. While the profitability variable is not proven to significantly affect the company's capital structure.